Prestressing of cold forging tools for parts with functional elements - Killmann, Martin; Merklein, Marion (XL. Colloquium on Metal Forming, 2022)
An increasing demand for complex part geometries poses challenges to the fatigue strength of cold forging tools. When producing functional elements like gears or carriers, local stress peaks occur in the forging dies. To avoid fatigue failure, an analysis of the stress state and adequate prestressing strategies for non-circular symmetrical cold forging tools are necessary. Therefore, a model process for the closed-die forging of four functional elements is introduced and the resulting stress state analysed numerically. While high compressive stresses and radial displacements are present between the functional elements, there is a tensile stress area with tangential stresses critical for fatigue failure at the head of the functional elements. To counteract this, a local prestressing of functional elements by stress pins is proposed. The pins are pressed into the tool, locally creating radial compressive and tangential tensile stresses. They are well suited for geometries with functional elements, because there are no undesired interactions between pin and process tensile stresses. Even the stress state in tools for more complex part geometries with a higher number of functional elements can be improved that way. However, the height of the local prestressing is still limited by tensile stresses around the pin. <
Keywords: Cold forging; tooling; prestressing; stress pins